Extrativismo e caracterização de acessos de Spondias Tuberosa arruda - Silva, Krisna Alves Batista da (2019)
The Caatinga is characterized by being one of the largest and most distinct phytogeographical regions, housing unique fauna and flora with many endemic species. One of these species is the umbu tree (Spondias tuberose Arr.), which has well defined characteristics besides presenting enormous commercial potential. There is a need for strategies aimed at the conservation of the umbu tree because of the enormous importance it has for extractivist communities that see this species as a source of income in the harvest period. In this context, this work sought through the analysis of the umbu tree productive chain, as well as the characterization of the fruits and the study of the genetic diversity among individuals to provide subsidies for strategies to better use the resource allied to the conservation of the species. For that, people directly involved in umbu tree extractivism were interviewed, belonging to the Flamengo community, from Jaguarari city (state of Bahia), where the study started. Posteriorly, fruits were collected from the same accessions that are used for commercialization. These fruits were submitted to biometric characterization and analysis of divergence, to investigate the genetic variability between accessions. From these analyzes, it was possible to verify that the informants have a strong relation with the umbu tree and the commercialization of its fruits. It was also possible to verify that among the analyzed accesses, there is a great potential for exploration in the genetic enhancement programs, as well as the use of the seeds, almost exclusive means of propagation.